تفعيل المناجمنت العمومي الجديد في المؤسسات الاستشفائية من خلال مشروع المؤسسة -دراسة حالة المؤسسة الاستشفائية العمومية بدلس -: Implementation of New Public Management in healthcare institutions through the corporate project -Case study of the public hospital of Dellys- - عقون سعاد; مقدود وهيبة (Journal of North African Economies, 2025)
The new public management is the best way to achieve a high-quality public service. allowing public institutions to overcome the various administrative complexities they are experiencing, through the adoption of sophisticated methods that allow rational decision-making and maximize benefits through the rational use of the resources at their disposal, including corporate project, which aims to achieve the best results for these institutions. As one of the most important of these institutions, the application of mines is of great importance, making it possible to provide services at the level of citizens' aspirations. This research aims to know the application of this tool in the Public Hospital of Dellys. And for this we introduced the concept of new public management first, then the corporate project as one of its applications in the field, and finally to see how it is applied in the study establishment. And we found that the latter applies the project in all its directions, and its efforts are in accordance with the directives of the Ministry of The Will, and this tool helped him to control his performance and activities.